Improvement of lean flame stability of inverse methane/air diffusion flame by using coaxial dielectric plasma discharge actuators. (1st May 2017) - De Giorgi, Maria Grazia; Ficarella, Antonio; Sciolti, Aldebara; Pescini, Elisa; Campilongo, Stefano; Di Lecce, Giorgio
Abstract: Low environmental impact is a main issue in the design of novel combustion systems, as aircraft engines. In this context, the present work investigates the possibility to increase the combustion efficiency of a lean flame through the use of sinusoidally driven dielectric barrier discharge (DBD) plasma actuator. The effect of the plasma discharge on a lean non premixed methane/air flame in a Bunsen-type burner has been studied for two different configurations: the normal diffusive flame (NDF) and the inverse diffusive flame (IDF). The flame behavior was investigated by chemiluminescence imaging through an intensified CCD camera. Optical filters were installed in front of the camera, aiming to selectively record signal from the chemiluminescent species OH*, CH*, or CO2 *. This allowed evaluating the changes occurring in presence of plasma actuation in term of flame emissions. It was shown that the plasma effects are significantly influenced by the burner and DBD configuration. A plasma power of approximately 25 W permitted to increase the air mass flow rate at which lean blowout appears; it rose up to 30% for low methane flow rate and up to 10% at high fuel flow rate. Highlights: A coaxial-cylinder dielectric barrier discharge is used on a CH4 /air Bunsen flame. DBD has a significant influence on the flame shape of both IDF and NDF flame. At low (O/F)mom DBD leads to the backward propagation of IDF flame. Chemiluminescence imaging underlines a rise of CO2 * with DBD. DBD leads to an evident improvement of the lean blowout limits.